Whisker electromyograms signify awake and anesthetized states in mice. (November 2019) - Noguchi, Asako; Sakaguchi, Tetsuya; Sato, Mototsugu; Aikawa, Hide; Matsumoto, Nobuyoshi; Ikegaya, Yuji
Highlights: We report a method to record whisker electromyograms in mice. We used the method to discriminate anesthetized or awake states. We also extracted respiratory rhythms from the electromyograms. Abstract: The behavioral state of animals is essential information for functional recordings of neuronal activity; practically, the exact timing when animals recover from anesthesia is important information. Recordings of cortical local field potentials and dorsal neck electromyograms (EMGs), a widely used method to identify behavioral states, requires at least two recording electrodes, one of which also requires a craniotomy procedure. In the present study, recordings of whisker EMGs alone are sufficient to detect the state switch from anesthesia to awakening in head-fixed mice. This method uses a single electrode and thus is technically simple and demands a less physical burden to animals. Moreover, whisker EMGs recorded under anesthesia reflect respiratory rhythms.